2015
DOI: 10.1111/eci.12482
|View full text |Cite
|
Sign up to set email alerts
|

sST2 levels are associated with all‐cause mortality in anticoagulated patients with atrial fibrillation

Abstract: In an anticoagulated AF patient's cohort, sST2 levels are an independent predictive factor of all-cause mortality. sST2 levels could be a biomarker used to improve clinical risk assessment in anticoagulated AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Our group [35] validated for the first time, the predictive value of sST2 in atrial fibrillation (AF) patients and concluded that sST2 levels had independent predictive value for all-cause mortality. Indeed, several groups have demonstrated the role of sST2 in cardiovascular events [36,37].…”
Section: Detection Of Central Venous Catheter-related Bloodstream Infmentioning
confidence: 96%
See 3 more Smart Citations
“…Our group [35] validated for the first time, the predictive value of sST2 in atrial fibrillation (AF) patients and concluded that sST2 levels had independent predictive value for all-cause mortality. Indeed, several groups have demonstrated the role of sST2 in cardiovascular events [36,37].…”
Section: Detection Of Central Venous Catheter-related Bloodstream Infmentioning
confidence: 96%
“…sST2 levels are associated with all-cause mortality in anticoagulated patients with atrial fibrillation [35] (Mar ıa Asunci on Esteve-Pastor and Francisco Mar ın)…”
Section: Detection Of Central Venous Catheter-related Bloodstream Infmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, sST2 may play part in the inflammatory process of diabetes mellitus, although the mechanisms behind this are not yet fully understood. Levels of sST2 have been associated with cardiovascular complications and mortality [20, 21] and suggested to have a prognostic value as risk predictor in patients with ambulatory chronic heart failure [22]. …”
Section: Introductionmentioning
confidence: 99%